Glycoconjugated Metallohelices have Improved Nuclear Delivery and Suppress Tumour Growth In Vivo - Song, Hualong; Allison, Simon J.; Brabec, Viktor; Bridgewater, Hannah E.; Kasparkova, Jana; Kostrhunova, Hana; Novohradsky, Vojtech; Phillips, Roger M.; Pracharova, Jitka; Rogers, Nicola J.; Shepherd, Samantha L.; Scott, Peter (Angewandte Chemie International Edition, 2020)
Monosaccharides are added to the hydrophilic face of a self‐assembled asymmetric FeII metallohelix, using CuAAC chemistry. The sixteen resulting architectures are water‐stable and optically pure, and exhibit improved antiproliferative selectivity against colon cancer cells (HCT116 p53+/+) with respect to the non‐cancerous ARPE‐19 cell line. While the most selective compound is a glucose‐appended enantiomer, its cellular entry is not mainly glucose transporter‐mediated. Glucose conjugation nevertheless increases nuclear delivery ca 2.5‐fold, and a non‐destructive interaction with DNA is indicated. Addition of the glucose units affects the binding orientation of the metallohelix to naked DNA, but does not substantially alter the overall affinity. In a mouse model, the glucose conjugated compound was far better tolerated, and tumour growth delays for the parent compound (2.6 d) were improved to 4.3 d; performance as good as cisplatin but with the advantage of no weight loss in the subjects. Asymmetric triplex metallohelices can be conjugated with sugars using post‐assembly CuAAC chemistry, to give optically pure architectures with anti‐cancer activity and marked selectivity with respect to non‐cancerous cell lines. Glucose‐appended structures exhibit improved nuclear uptake in vitro and supress tumour growth in vivo.